2022
DOI: 10.3390/ijerph191811691
|View full text |Cite
|
Sign up to set email alerts
|

Parental Psychological Control and Children’s Prosocial Behavior: The Mediating Role of Social Anxiety and the Moderating Role of Socioeconomic Status

Abstract: Complementing internalizing and externalizing developmental outcomes of parental psychological control, in this study, we shift the focus to children’s prosocial behaviors. Drawing on self-determination theory and problem-behavior theory, this study addresses the relationship between parental psychological control, social anxiety, socioeconomic status (SES), and children’s prosocial behavior. The parental psychological control scale, social anxiety scale for children, and prosocial behavior were applied in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 55 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Recent research endeavors in developmental psychology have demonstrated a clear evolution in the field's perspectives and methodologies. From exploring the implications of evolutionary theory in understanding human behavior (Goetz et al, 2022;Narvaez et al, 2022) to delving into the impact of parental influences on children's development (Zhang et al, 2022), scholars are continually pushing the boundaries of traditional developmental psychology. The incorporation of diverse theoretical frameworks and empirical approaches has not only enriched the field but has also opened up new avenues for research and practice.…”
Section: Abstract: Methodology Developmental Psychology Perspectivesmentioning
confidence: 99%
“…Recent research endeavors in developmental psychology have demonstrated a clear evolution in the field's perspectives and methodologies. From exploring the implications of evolutionary theory in understanding human behavior (Goetz et al, 2022;Narvaez et al, 2022) to delving into the impact of parental influences on children's development (Zhang et al, 2022), scholars are continually pushing the boundaries of traditional developmental psychology. The incorporation of diverse theoretical frameworks and empirical approaches has not only enriched the field but has also opened up new avenues for research and practice.…”
Section: Abstract: Methodology Developmental Psychology Perspectivesmentioning
confidence: 99%
“…The prevalence of this disorder in Iranian society shows a 10.1% prevalence, with women being more affected than men (You et al, 2019). If untreated, this disorder is accompanied by a chronic and covert course (Lamb, 2009), causing fundamental disorders in work, social fields, academic functions, family, and personal life, leading to a decrease in the individual's quality of life (Xu et al, 2017;Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding gender, studies indicate that females tend to spend more time on VSNs connecting with strangers, engaging in discussions with friends and relatives, and expressing heightened concern when lacking Internet access (Ballesta-Pagán et al, 2021). Additionally, there seems to be limited parental oversight regarding their children's access to VSNs, irrespective of gender (Zhang et al, 2022). In relation to dangerous practices associated with ICTs and VSNs, high school students might exhibit violent attitudes and find themselves in dangerous online situations (Masrom et al, 2021).…”
Section: Introductionmentioning
confidence: 99%